Kecemasan Masyarakat Terhadap Covid-19 Berdasarkan Usia dan Zona Tempat Tinggal - Roby Maiva Putra; Zulfan Saam; Raja Arlizon (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2021)
The current study aims to identified and described the differences in the level of public anxiety concerning the COVID-19 pandemic based on age and residential zone and the implications for guidance and counseling. This research used a quantitative approach with a comparative descriptive method. The population in this study were the people of 12 districts/cities in Riau Province with the sampling technique using simple random sampling which obtained a sample of 200 people ranging from adolescence to senior with details of 100 people coming from the red zone and 100 people from the green zone of COVID-19 transmission. The research instrument used a Likert-scale questionnaire on the level of public anxiety. The questionnaire was distributed using the google form and the data collection was conducted start from April until May 2020. The results of this study indicated that: (1) the public's anxiety concerning COVID-19 pandemic categorized as moderate; (2) public anxiety concerning COVID-19 pandemic with the highest percentage emerges in the senior category; (3) there was a significant difference between the level of anxiety of people living in the green zone and the red zone concerning COVID-19. These results can be used as references in making guidance and counseling programs in educational units, counseling organizations, and the government as a foundation for a policy brief in dealing with the COVID-19 pandemic.